Production and distribution of value - Villalobos Céspedes, Daniel (2022)
The fundamental contribution of this research is regarding five of Cobb and Douglas’s core questions that we believe the theory of economic growth has not made clear until now. The answers we provide are an attempt to measure relative and total resource contribution to production growth and its distribution between them. It implies paying close attention to the latest refinement of the theory and dealing with new critical assumptions, key formulas, and method of attack. The evaluation of these efforts by Cobb and Douglas’s data support the hypothesis that distribution processes are modeled by those of the production of value. The scope of this research could motivate further progress in the study of economic growth.